Guide to Legislative Drafting in Kurdistan Regional Government - Cuvillier, Emmanuel (World Bank, Washington, DC, 2015)
The development of a regulatory framework which meets international standards is a major concern in the Middle East and North Africa (MENA) region, as it is key not only to fostering economic development but also to ensuring the wellbeing of its citizens. To achieve this goal, it is important to: create a sound institutional structure; employ staff qualified in law drafting; set up efficient procedures for co-ordination and consultation; and ensure that the possible impact of new legal instruments is assessed before adopted. The prime objective of the World Bank in supporting the KRG Shura Council remains an improved guide consistent with international standards that can be used by all relevant parties in charge of drafting all types of legislation in the KRG. In keeping with better regulation principles, the authority and impact of the guide are to be achieved more by the relevance of its contents and the quality of its practical advice than by the strength of the legal instrument that seeks to enforce it. This will help to maximize the benefits of the guide in the KRG. In this context, the official use of the guide to legislative drafting should become mandatory. This could be achieved either through making the guide an integral part of a new law on legislative drafting to be passed by the parliament in the KRG under penalty of 0ity of any draft law that violates this rule.